Turkmenistan and military buildup in the caspian region: A small state in the post-unipolar era - Dmitry Shlapentokh (Journal of Eurasian Studies, 2013)
Caspian Sea had been actually a Soviet internal lake. Iran was too weak to be a competitor/rival for the USSR. The collapse of the USSR had transformed Caspian Sea into the sea surrounded by several states and each of them vie for the Caspian Sea’s natural resources. Caspian Sea became also important as the route for delivery of oil/gas. All of this led to considerable tensions among the states in the area and naval buildup. Even Turkmenistan, desert republic, started to build the navy and contribute to the rise of tension in Caspian Sea. All of this indicated the increasing global instability which followed the end of Cold War and the end of the USA unipolarity.